Geospatial Information: A Success Factor for Sudan’s Hydrologic Investigations - Sami, Kamal; Barsi, Babiker Ibrahim (University of Khartoum Engineering Journal, 2025)
— Hydrologic investigations and analysis are essential components of any water resources assessment. Traditionally, these investigations require significant time, effort, and financial resources. However, the emergence of remote sensing techniques, along with geospatial data and information, has provided new sources of hydrological data and significantly enhanced the capabilities of water resources assessments. The primary objective of this article is to highlight the significance of geospatial data and information in the success of hydrologic investigations and hydraulic designs. The study also provides valuable information to assess the current situation and the data available for future research. Elevation data is derived from the default ALOS World3D (AW3D) Digital Elevation Model (DEM) readings. This paper demonstrates that feasibility studies for water harvesting projects can be effectively conducted using geospatial and remote sensing data. As an illustration of the potential of these technologies, a case study is presented, detailing hydrologic investigations and engineering designs for multiple water harvesting projects and water supply systems serving 14 towns and 26 villages in West Kordofan State - Sudan. Based on the outcome of this study, the authors call for the development of a unified geospatial information system for hydrology, water resources, water harvesting for agriculture and animal production, and the production of flood risk maps in Sudan